Polycystic Ovary Syndrome in Teenage and Young Women - Nahar, Kamrun (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Polycystic ovary syndrome (PCOS) is an inherent ovarian dysfunction. It is a common health problem that can affect teen girls and young women. PCOS is characterized by hyperandrogenism, irregular ovulatory cycle and metabolic derangement , including glucose intolerance and hyperinsulinaemia. Hyperandrogenism is a clinical hallmark of PCOS. Hypersecretion of androgen by the stromal theca cell of polycystic ovary is cardinal clinical manifestation. Though the exact cause of PCOS is not known , the syndrome can result from disturbance in the hypothalamo pituitary ovarian axis and hyperinsulinaemia. Several definitions have been produced to describe the disease. European society of human reproduction and embryology and the American society for reproductive medicine in 2004 define PCOS as manifestation of two of the following three J Bangladesh Coll Phys Surg 2019; 37(2): 78-82